Stagnation in Flood Governance Policy: An Analysis of the Draft Regional Regulation on Flood Management in Bontang City - yassier arafat; Bambang Irawan; Cathas Teguh (Indonesian Journal Publisher, 2026)
This study examines the interrelation between political dynamics, institutional stagnation, and governance innovation within the formulation and evaluation of local policies, with a specific focus on the Flood Management Draft Regulation. The research aims to explore how political and bureaucratic structures influence policy coherence and the extent to which institutional mechanisms either facilitate or hinder adaptive reform. The analysis highlights that local policy processes are often dominated by political interests that restrict institutional flexibility, leading to procedural formalism and limited innovation. The substantive evaluation of the flood management regulation reveals that despite the inclusion of technical and preventive measures, the lack of interagency coordination and fiscal autonomy undermines policy effectiveness. The implications for local governance emphasize the importance of leadership vision, accountability, and participatory engagement as drivers of institutional transformation. The study employs a qualitative descriptive approach combined with thematic analysis using the Miles and Huberman model, enabling an in-depth exploration of patterns, meanings, and relationships across policy documents, institutional behaviors, and governance practices. The findings suggest that sustainable governance innovation arises from the systemic alignment of political will, institutional learning, and evidence-based policymaking, positioning local governments as adaptive entities capable of addressing environmental and administrative complexities.